2018
DOI: 10.1002/hc.21452
|View full text |Cite
|
Sign up to set email alerts
|

π‐Dimerization ability of conjugated oligomer dication diradicaloids composed of dithienylpyrrole and benzodithiophene units

Abstract: Stable conjugated oligomer dications 12+ and 22+ composed of 2,5‐di(2‐thienyl)‐N‐methylpyrrole (DTP) units at the both ends of the π‐systems with methoxy substituents at the 3‐position of thienyl units and methylthio end‐capping group and benzo[2,1‐b:3,4‐b′]dithiophene (BDT) unit(s) at the central part with sterically demanding phenyl substituents were synthesized. From DFT calculations and ESR experiments, it was concluded that the diradical character in 12+ and 22+ was reduced in comparison with the radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We are interested in the basic properties and their applications to supramolecular chemistry of the -dimers of conjugated oligomer radical cations. [24][25][26][27][28][29][30][31] As such, AuNP 1 protected by thiolates of methylthio end-capped quaterthiophene partially annelated with bicyclo[2.2.2]octene unit (Figure 1) was prepared in our previous study. 32 The conductivity of drop-cast film of 1 was below the measurement limit (<10 ;& S cm ; ) of the ; monitor and interdigitated array (IDA) electrode used, while more than 10 4 -fold enhancement of conductivity was recorded after exposure of iodine vapor to the film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in the basic properties and their applications to supramolecular chemistry of the -dimers of conjugated oligomer radical cations. [24][25][26][27][28][29][30][31] As such, AuNP 1 protected by thiolates of methylthio end-capped quaterthiophene partially annelated with bicyclo[2.2.2]octene unit (Figure 1) was prepared in our previous study. 32 The conductivity of drop-cast film of 1 was below the measurement limit (<10 ;& S cm ; ) of the ; monitor and interdigitated array (IDA) electrode used, while more than 10 4 -fold enhancement of conductivity was recorded after exposure of iodine vapor to the film.…”
Section: Introductionmentioning
confidence: 99%
“…We are interested in the basic properties and their applications to the supramolecular chemistry of the π-dimers of conjugated oligomer radical cations. 24–31 As such, AuNP 1 protected by thiolates of methylthio end-capped quaterthiophene partially annelated with bicyclo[2.2.2]octene units (Fig. 1) was prepared in our previous study.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,10,12 Oligothiophene-and oligopyrrole derivatives are a further very successful concept for p-dimerization of radical cations. [14][15][16][17][18] Some studies also suggested the occurrence of s-dimerization. 19,20 p-dimerization of radical cations was also observed for thienoacenes, 21 while the related thiophene-based [n]helicenes show little tendency towards radical cation dimerization.…”
mentioning
confidence: 99%